2011
DOI: 10.1007/s00125-011-2289-z
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin occupancy of transcription factor 7-like 2 (TCF7L2) and its role in hepatic glucose metabolism

Abstract: TCF7L2 is an important regulator of HGP in vitro and binds directly to genes that are important in pathways of glucose metabolism in the liver. These data highlight the possibility that TCF7L2 may affect fasting and postprandial hyperglycaemia in carriers of at-risk TCF7L2 genetic polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 42 publications
6
88
1
1
Order By: Relevance
“…Recent reports have shown that mouse TCF7L2 expression is insulin-responsive [20,22] and that in insulin-resistant mice expression of the short and medium C-terminal transcripts (e.g. including T3 and T5) was reduced [21]. Our data on human liver transcript expression show that the expression of five liver TCF7L2 transcripts (T2, T4, T7, T8, T9) was increased in type 2 diabetic compared with normoglycaemic individuals.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Recent reports have shown that mouse TCF7L2 expression is insulin-responsive [20,22] and that in insulin-resistant mice expression of the short and medium C-terminal transcripts (e.g. including T3 and T5) was reduced [21]. Our data on human liver transcript expression show that the expression of five liver TCF7L2 transcripts (T2, T4, T7, T8, T9) was increased in type 2 diabetic compared with normoglycaemic individuals.…”
Section: Discussionsupporting
confidence: 50%
“…Transcription of some genes may be directly regulated by TCF7L2 binding to their promoter and/or enhancer sequences, as has been reported for PCK1 and GYS2, while others (G6PC) have not been reported to have TCF7L2 recognition sites [21,[31][32][33]. Therefore, we analysed the role of TCF7L2 in the HNF4α-FOXO1-mediated transcriptional regulation of G6PC.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations